Failure analysis of a C-type bourdon tube (2024)
ABSTRACT: This paper presents the failure analysis of a C-type Bourdon tube made of AISI 316L stainless steel, which was part of a pressure gauge. For the study, chemical composition and microstructure of the Bourdon tube were determined. Additionally, electrochemical attack with oxalic acid was used to assess if the microstructure was suspected of sensitization in samples taken near to and away from the failure. Finally, fractographic analysis of the failed Bourdon tube was accomplished by scanning electron microscopy. The results showed that the failure was due to an intergranular corrosion phenomenon that embrittled the material in the area close to the welding between the Bourdon tube and the joint.